Excess currents in planar Ba(Fe1−xCox)2As2/TiOx/Pb Josephson junctions. Issue 12 (3rd September 2015) - Döring, Sebastian; Reifert, David; Hasan, Noor; Schmidt, Stefan; Schmidl, Frank; Tympel, Volker; Kurth, Fritz; Iida, Kazumasa; Holzapfel, Bernhard; Wolf, Thomas; Seidel, Paul
Abstract: We prepared planar hybrid Josephson junctions using Co‐doped BaFe 2 As 2 thin films and polished single crystals as base electrode, sputtered, and subsequently oxidized titanium layers as barrier and a counter electrode from evaporated lead. On all junctions, RCSJ‐like current–voltage characteristics could be observed. The obtained I c R n products at 4.2 K range up to 95 μ V for thin film junctions and up to 1.15 mV for junctions on single crystals. For most of the junctions, an excess current with variable contribution to the total current could be observed. Unusual temperature dependencies are discussed for the critical and the excess currents, respectively. Investigations of the junctions under microwave irradiation were performed, therein Shapiro steps up to high orders and very clear modulations of the steps could be observed. Additionally, the origin of the excess current is discussed with respect to the microwave dependence. Furthermore, instead of a single junction, a network‐like modulation behavior of the critical current in magnetic fields was observed.